Policing The Police in Malaysia: Comparative Views - Ayub, Zainal Amin; Wahab, Harlida Abdul; Yusoff, Zuryati Mohamed; Zan, Zainal Md; Shariffuddin, Mohd Dino Khairri (CENTRAL ASIA AND THE CAUCASUS, 2021)
Integrity is a key factor in determining the success and progress of a country. Emphasis on integrity has become the government's main agenda. Enforcement agencies are the forerunners of the community service delivery system and ensure that the public is in compliance with applicable laws and regulations. However, enforcement agencies are also identified as vulnerable and high-risk agencies to engage in the wrongdoings, abuse of power and corruption. In Malaysia, the Enforcement Agency Integrity Commission is responsible to oversee and enforce integrity complaint against 21 enforcement agencies. In Australia, the enforcement integrity commission called Australian Commission for Law Enforcement Integrity is responsible for regulating five enforcement agencies including the Australian Federal Police but only focuses on corruption practices. While in Hong Kong, Independent Police Complaints Council plays the role of monitoring police force and involve the investigation of all complaints against the police. Therefore, this article aims to see the effectiveness of the integrity commission through the number of complaints and investigations recorded. Accordingly, a comparison has been made to the three integrity commissions involved in respective countries. This article adopts a doctrinal research methodology which mainly library research that adopting secondary sources. This article finds that in other jurisdictions, most complaints of abuse by enforcement agencies are investigated by the agencies themselves; while in some jurisdictions, the supervisory commissions only act in the cases that involving serious misconduct. Also, the article finds that the commissions in these jurisdictions only have supervisory power in. advising the enforcement agencies to take disciplinary action against the wrongdoers. The role of enforcement agency as such is wider as compared to their peers in other jurisdictions.